PREDICTION OF THROMBOEMBOLISM IN PATIENTS WITH LONG-LASTING ATRIAL FIBRILLATION - R. D. Kurbanov; N. J. Zakirov; D. B. Irisov; Sh. S. Khusanov (Евразийский Кардиологический Журнал, 2014)
The aim of the study. Comparative analysis of the risk assessment of thromboembolism by CHADS2 and CHA2DS2-VASc scores, and to study the preventive effectiveness of different antithrombotic agents in patients with long-lasting аtrial fibrillation (AF) at 1 year follow-up. Materials and methods. The study included 108 patients aged 38 to 78 years old (mean age 62,6±8,4 years) with persistent or permanent AF. In 93.5% of patients revealed coronary artery disease and / or arterial hypertension, in 6.5% - non-coronary heart diseases. The risk of tromboembolism assessed by CHADS2 and CHA2DS2-VASc scores. Results. Patients at low risk of tromboembolism, according to CHADS2 score was 2.8%, in their absence, on a CHA2DS2-VASc score. Patients with moderate risk of tromboembolism, in these scores were 63.9% and 7,4% (χ2=72.653; p=0.000) respectively, and a high risk of tromboembolism - 33,3% and 92,6% (χ2=78,796, p=0.000) respectively. Depending on the ways to prevent tromboembolism, patients were divided into 2 groups. 1st group included patients treated with warfarin (n=90), and the endpoints were observed in 5.6% of patients. 2nd group included patients (n=18) treated with acetylsalicylic acid (ASA) and the end point was observed in 27.8% of patients. Conclusion. The introduction of a new CHA2DS2-VASc score led to an increase number of patients, who need mandatory anticoagulant therapy by 2.8 times. In the group of patients with atrial fibrillation treated with warfarin compared with a group of patients treated with aspirin, where cases of ischemic stroke have developed less often, and their clinical manifestation are less pronounced and are characterized by a benign course.